The Influence of an Active Glove Arm in Softball Pitching: A Biomechanical Evaluation - Barfield, Jeff W.; Anz, Adam W.; Osterman, Catherine L.; Andrews, James R.; Oliver, Gretchen D. (International Journal of Sports Medicine, 2019)
The purpose of this study was to determine whether glove arm kinematics during a windmill softball pitch impact pelvic and trunk kinematics as well as pitching arm shoulder kinetics. Thirty-Nine college softball pitchers (20.0±1.4 yrs.; 174.7±6.1 cm; 82.0±13.0 kg; 10.7±2.7 yrs. of experience) threw 3 pitches to a catcher while kinematic and kinetic data were collected. Pearson product moment correlations were run, and significant correlations found with glove arm kinematics, occurring before pelvis kinematics, trunk kinematics, and shoulder kinetics, were then put through a linear regression to identify whether there was any potential cause and effect. Results revealed that glove arm elbow flexion during phase 1 significantly predicted normalized shoulder rotation moment during phase 4 (t=2.60, p=0.013). Additionally, glove arm shoulder horizontal abduction during phase 1 significantly predicted normalized shoulder moment in phase 3 (t=− 2.40, p=0.021) and pelvic angular velocity during phase 3 (t=−  3.20, p=0.003). In conclusion, an active glove arm was predictive of a more efficient kinetic chain later in the windmill pitching motion and could possibly play a role in preventing injury by lessening pitching shoulder joint loads.
Keywords: kinematics; kinetics; pitching; shoulder injury; shoulder internal rotation; softball